2012
DOI: 10.1159/000335172
|View full text |Cite
|
Sign up to set email alerts
|

The Exon 3-Deleted/Full-Length Growth Hormone Receptor Polymorphism and Response to Growth Hormone Therapy in Growth Hormone Deficiency and Turner Syndrome: A Multicenter Study

Abstract: Background/Aim: The exon 3-deleted/full-length (d3/fl) growth hormone (GH) receptor (GHR) polymorphism has been associated with responsiveness to GH therapy in some diagnostic groups. However, there are still controversies on this issue. To evaluate the effect of the GHR exon 3 polymorphism on growth after 1 and 2 years of GH therapy in Turkish patients with GH deficiency (GHD) and Turner’s syndrome (TS) and the distribution of GHR exon 3 isoforms. Materials and Methods: 218 patients with GHD (125 males/93 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 74 publications
(75 reference statements)
0
15
1
6
Order By: Relevance
“…Four studies have investigated this SNP alone 15,17,19 and three, its role alone and in combination with polymorphisms in the VDR (vitamin D receptor), IGFBP3 (insulin-like growth factor binding protein) and SOCS2 (suppressor of cytokine signaling) genes, via gene-gene interaction. Three possible genotypes can be observed: fl/fl, fl/d3 and d3/d3, with the latter being the one with the lowest frequency.…”
Section: Short Staturementioning
confidence: 99%
See 1 more Smart Citation
“…Four studies have investigated this SNP alone 15,17,19 and three, its role alone and in combination with polymorphisms in the VDR (vitamin D receptor), IGFBP3 (insulin-like growth factor binding protein) and SOCS2 (suppressor of cytokine signaling) genes, via gene-gene interaction. Three possible genotypes can be observed: fl/fl, fl/d3 and d3/d3, with the latter being the one with the lowest frequency.…”
Section: Short Staturementioning
confidence: 99%
“…20,21 One of the studies 20 mentioned that the possible reasons for the lack of correlation in two previous studies included the small number of patients evaluated 18 and the fact that few individuals are carriers of the d3 allele. 17,20 One way to increase sample size is to perform multicenter studies, such as those carried out by Ko et al 17 and Baş et al, 19 both retrospective. 17 The three studies that showed negative association of the d3-GHR polymorphism were carried out in Korea, Venezuela and Turkey.…”
Section: Short Staturementioning
confidence: 99%
“…During the last decade many studies showed growth hormone (GH) treatment as safe and effective for growth promotion in TS. Table 2 presents the results of growth therapy and indicates positive, negative and neutral determinants of therapy effectiveness as well as consequences and side effects of hormonal therapy in the analysed articles (4,5,7,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50).…”
Section: Growth and Growth Therapy And Consequencesmentioning
confidence: 99%
“…Örneğin, BH reseptorü ekzon 3 delesyon polimorfizmi (32,33) veya IGFBP-3 promotor geni -202 A polimorfizminin (34) özellikle ağır BHE vakalarında BH tedavi yanıtını artırabileceği öne sürülmektedir. Bu konunun ayrıntıları bu derlemenin kapsamı dışın-da olup, bu konuda çalışmalar devam etmektedir (35) .…”
Section: Dönemlerunclassified